Factors affecting cost of gain of feedlot steers - Albright, M.; Schroeder, Ted C.; Langemeier, Michael R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This study examined the relative effects of corn price and cattle performance factors on steer finishing cost of gain. Seasonal analysis of cost of gain and the factors affecting it was also conducted. Using over 10 years of closeout data from two western Kansas feedyards, corn prices, feed conversion, and daily gain explained 93 to 94% of the variation in steer finishing cost of gain. About 60% of the variability was explained by corn price alone. Cost of gain and feed conversion rates were seasonally below average for steers placed in February through August. Daily gain was seasonally high for steers placed in March through August. Because cost of gain is heavily influenced by the volatility and seasonal patterns of corn price and cattle performance, cattle feeders should consider this information when making placement decisions.
Keywords: Beef; Feedlot cattle; Cost of gain; Feed conversion; Daily gain